Prospective impact of individual, family and community youth assets on adolescent suicide ideation. Issue 3 (23rd November 2018) - Lensch, Taylor; Clements-Nolle, Kristen; Oman, Roy F; Lu, Minggen; Dominguez, Amanda
Abstract : Background: Studies have found that youth assets have a protective influence on many risk behaviours. However, the relationship between youth assets and adolescent suicide ideation is poorly understood. The purpose of this study was to determine if youth assets were prospectively associated with suicide ideation. Methods: Four waves of data were collected from 1111 youth and their parents living in randomly sampled census tracts that were stratified by income and race/ethnicity using census data. Computer-assisted, in-person data collection methods were used to measure assets at the individual (6 assets), family (4 assets) and community (6 assets) levels. Generalised linear mixed models were used to prospectively assess the relationship between the number of individual-level, family-level and community-level assets and suicide ideation, while controlling for known confounders. Results: About half of the sample was female (53%). Participants were racially/ethnically diverse (white (41%), Hispanic (29%) and black (24%)). Eleven of the 16 assets were associated with reduced odds of suicide ideation. In addition, there was a graded relationship between the number of assets at each level (individual, family and community) and the odds of suicide ideation. For example, compared with youth with 0–2 family assets, those with 3 (OR 0.61; 95% CI 0.42 to 0.90) or 4 (OR 0.32; 95% CI 0.21 to 0.51) family assets had lower odds of suicide ideation. Conclusions: This prospective analysis showed a protective relationship between youth assets and suicide ideation, with the greatest protection among youth with the most assets. Interventions designed to build youth assets may be a useful strategy for reducing adolescent suicide ideation.